FREEDOM FRANCHISING AS AN ALTERNATIVE TO THE CLASSIC FRANCHISING - L. A. Solovova (Модернизация, инновация, развитие)
The article is devoted to the model of freedom franchising and to its comparison with the classic franchising model. The aim of the article is to systemize and enrich the knowledge in the sphere of the franchising model evolution. The author’s task was to identify the key features of the freedom franchising model, to compare the freedom franchising with classic franchising and to formulate the conditions under which the freedom franchising model can be developed. To achieve this the analysis, synthesis, comparison and longitude methods were used. Classic franchising model includes the transfer of both visible (design, brand style) and invisible to the customers (business processes, know-how) elements from the franchisor to the franchisee. Such a business model enables the franchise to preserve the high quality of products and services and to grow the net at high rate. The drawback of the classic model is the complexity of bringing up innovations by the franchisee – new ideas are strictly chosen by the franchisor and then implemented within the network only after the successful experience in control points of contact. Nevertheless, there is the franchising business model in which franchisees can experiment with front-of-house (visible) elements of the system (such as point’s of contact design) on the one hand, and on the other – in which new ideas and initiatives from the franchisee are welcomed by the franchisor. The model is called “freedom franchising”. It is important to point out that key system elements are standardized in both models as standardized production processes help preserve high quality within the franchising net. Freedom franchising model is not applicable in the spheres where full business standardization is needed as well as in the business that is focusing on fast growth. But it helps franchisees to implement new ideas within the whole network. The article would be of interest to franchisors for creating franchise programs as freedom franchising model helps combine the regulations of the franchising model with franchisees’ initiatives.